Effectiveness of the “Jalin Matra” Material in Poverty Management A Case Study of Turi Village, Jetis District, Ponorogo Regency, East Java Province, Indonesia - Dwi Poernomo, - (Science and Technology Publications, Lda, 2018)
Jalan Lain Menuju Mandiri dan Sejahtera (“JALIN MATRA”) Program is a poverty alleviation program that has been implemented by the Government of East Java Province and contains micro data of East Java Province obtained through census by name and address of households with the lowest welfare status. In 2016, the program was still not well implemented since there were conflicts in its legislation requiring the currently implemented mechanism to be adjusted. It was started from providing cash assistance to impoverished households, into providing the goods assistance by the village government. The study aimed to assess the effectiveness of “Jalin Matra” Program as a poverty alleviation effort at East Java Province in 2016 to be used as a consideration for the program sustainability. The method used in this study is socio-legal research in which the review of legislation as the legal basis of the “Jalin Matra” Program is further confirmed by a field research through interviews with targeted household beneficiaries. The result is in accordance with what the aid providers expected that is the head of household beneficiaries are satisfied with the “Jalin Matra” Program and a positive impact on the household economy can be provided by the program. It is concluded that “Jalin Matra” Program has been effective to alleviate poverty in East Java Province and it can be one of the reference programs for poverty alleviation in other area, with a proper adjustment related to the special condition and characteristic of each region